2016
DOI: 10.1186/s13064-016-0076-8
|View full text |Cite
|
Sign up to set email alerts
|

Akirin2 is essential for the formation of the cerebral cortex

Abstract: BackgroundThe proper spatial and temporal regulation of dorsal telencephalic progenitor behavior is a prerequisite for the formation of the highly-organized, six-layered cerebral cortex. Premature differentiation of cells, disruption of cell cycle timing, excessive apoptosis, and/or incorrect neuronal migration signals can have devastating effects, resulting in a number of neurodevelopmental disorders involving microcephaly and/or lissencephaly. Though genes encoding many key players in cortical development ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
58
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(77 citation statements)
references
References 74 publications
16
58
3
Order By: Relevance
“…Together with prior studies in other cell types identifying Aki2 as a master regulator of gene expression, our data indicate that Aki2 controls the proper expression of key factors that drive mammalian myogenesis. Interestingly, a recent study reported that deletions in human chromosome 6q11‐15, which contains the Aki2 gene among several others, is associated with developmental delay, abnormal skull shape, dysplastic outer ear, and hypotonia (Engwerda et al, ), phenotypes potentially consistent with what we observe here and elsewhere (Bosch et al, ) in mice.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Together with prior studies in other cell types identifying Aki2 as a master regulator of gene expression, our data indicate that Aki2 controls the proper expression of key factors that drive mammalian myogenesis. Interestingly, a recent study reported that deletions in human chromosome 6q11‐15, which contains the Aki2 gene among several others, is associated with developmental delay, abnormal skull shape, dysplastic outer ear, and hypotonia (Engwerda et al, ), phenotypes potentially consistent with what we observe here and elsewhere (Bosch et al, ) in mice.…”
Section: Discussionsupporting
confidence: 92%
“…The loss of Aki2 in Aki2 SimKO mutants resulted in cell death, especially in the dermomyotome region in which Pax3 is expressed. This is a finding reminiscent of our prior work on corticogenesis (Bosch et al, ), where we showed that massive cell death occurred in the telencephalon within 12 hr after Emx1‐Cre ‐mediated Aki2 deletion. In addition, other studies suggest that an important functional role for Aki2 occurs during rapid proliferation of cells in response to a stimulus (Komiya, Akiyama, Sakumoto, & Tashiro, ; Komiya et al, ; Tartey et al, ), consistent with our observations.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations